2019
DOI: 10.3892/or.2019.7411
|View full text |Cite
|
Sign up to set email alerts
|

Cholinergic α5 nicotinic receptor is involved in the proliferation and invasion of human prostate cancer cells

Abstract: Nicotinic acetylcholine receptor (nAChR) subunit α5 (α5-nAChR) is involved in tumor cell proliferation, inhibition of apoptosis, progression of metastasis, and induction of angiogenesis in certain solid tumors. However, the role of α5-nAChR in prostate cancer cell growth and metastasis is unclear. In the present study, the role of α5-nAChR in cell proliferation, migration, invasion and apoptosis was investigated by silencing the expression levels of α5-nAChR in the prostate cancer cell lines DU145 and PC3. A s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…Interestingly, it was demonstrated that the SIRT5/PI3K axis mediated extremely high levels of IL-1β mRNA and protein in SIRT5 KO cells. Positive transcriptional regulators of this pathway, such as p50/65, were also induced in SIRT5 KO cells (40). IL-1β expression is positively correlated with bone metastasis in breast cancer, wherein IL-1β up-regulates VEGF and its corresponding receptor on endothelial cells to facilitate EC migration (41).…”
Section: Discussionmentioning
confidence: 98%
“…Interestingly, it was demonstrated that the SIRT5/PI3K axis mediated extremely high levels of IL-1β mRNA and protein in SIRT5 KO cells. Positive transcriptional regulators of this pathway, such as p50/65, were also induced in SIRT5 KO cells (40). IL-1β expression is positively correlated with bone metastasis in breast cancer, wherein IL-1β up-regulates VEGF and its corresponding receptor on endothelial cells to facilitate EC migration (41).…”
Section: Discussionmentioning
confidence: 98%
“…To assess the precise role of α5-nAChR in PCa, siRNA was used to silence α5-nAChR in PCa cell lines, DU145 and PC3. Results demonstrated that knockdown of α5-nAChR causes reduced levels of phospho-AKT and phospho-ERK1/2, followed by a significant decrease in cell migration and invasion and an induction of apoptosis, indicating the impact of α5-nAChR on the proliferation and invasion of human PCa cells and the importance of its silencing in PCa treatment [43]. Finally, six transmembrane epithelial antigens of the prostate 1 (STEAP1) was shown to be overexpressed in various types of tumors, particularly in PCa, and knockdown of STEAP1 in LNCaP cells by siRNA decreases cell viability and proliferation, whilst promoting apoptosis [44].…”
Section: Sirna-mediated Cancer-associated Gene Silencing In Prostate Cancermentioning
confidence: 97%
“…Macrophage-capping protein (CAPG) Reduces proliferatory, migratory, and invasive capacities of DU145 cells [54] Nicotinic acetylcholine receptor (nAChR) Decreases cell migratory and invasive activities, and induces apoptosis of DU145 and PC-3 cells. [43] Six transmembrane epithelial antigen of the prostate 1 (STEAP1)…”
Section: Sirna-target Gene Knockdown Consequencesmentioning
confidence: 99%
“…The subunit α5 of nAChRs as an important member of the nAChR family is involved in the proliferation and invasion of human PCa cells. 12 Magnon et al reported that autonomic nerve development contributes to PCa initiation and dissemination. 67 In this study, through the use of animal models of PCa, the authors demonstrated the role of the parasympathetic nervous system (PNS) in PCa development and progression.…”
Section: Prostate Cancermentioning
confidence: 99%
“…Nicotinic receptors express by many different types of genitourinary cells such as kidney, 10 bladder, 11 prostate, 12 testicular, 13 penile, 14 cervical, 15 ovarian, 16 uterine, 17 as well in their cancerous cells. Among the different subunits of nAChR, previous reports indicated that the nAChRs are associated with different genitourinary cancersrelated properties including CSC renewal, proliferation, metastasis, angiogenesis, and suppression of apoptosis (Figure 2).…”
Section: Introductionmentioning
confidence: 99%